FACTORS OF CONDUCTING PEACEKEEPING MISSIONS AND PECULIARITIES OF DIFFERENT POLICE STRUCTURES COEXISTENCE OF REPRESENTATIVES : THEORETICAL AND LEGAL STUDY (Bulletin of criminological association of Ukraine, 2022)
The scientific article uses an interdisciplinary method of scientific research,which helped to identify the methodology of achieving peace and security from a variety of positions of human psychology, traditional customs and cultural characteristics of peoples, which will inevitably be reflected in administrative law,namely makingthe right management decisions. It is emphasized that the successful organization of work taking into account the peculiarities of administrative, legal and administrative components will certainly give results.Peculiarities of coexistence of multinational communities in hotspots impose responsibilities of a socio-psychological nature and can cause a significant public response in the event of improper behavior of peacekeepers. Hence, the balance and proportionality of the interests of the state in whichsuch a mission is carried out and the personal and cultural factors, which later grow into a larger scale of social significance, deserve attention. It is necessary to form a general state policy on the most general strategic and tactical levels of peacekeeping missions, which largely depends on the leaders and the desire to take the initiative personally by each peacekeeper.
Keywords: peace, security, democratic processes, spiritual and cultural component, methods.